Performance of Carbon and Glass Fibre Composite Concrete Beams with Different End Anchorages - Hiew, Kee; Lloyd, Natalie; Chandler, Ian (Research Publishing, 2011)
The use of composite materials such as glass fibre and carbon fibre to enhance the strength of concrete structures has been adopted in construction practice, for both internal reinforcement and external retro-fitting of existing structures. Hence, fibre reinforced polymer (FRP) has been identified as a promising material. However, there are still areas of external fibre strengthening which require further research, especially the use of different end anchorage systems with which to secure the fibre polymers to the concrete structures. Failure of the bond between the fibre and concrete can lead to a brittle and sudden failure. Research was undertaken to evaluate the flexural performance of 12 large scale steel reinforced concrete beams with externally applied Carbon Fibre Reinforced Polymer (CFRP) and Glass Fibre Reinforced Polymer (GFRP).Different end anchorages and application configurations of the externally bonded glass and carbon fibres were evaluated to assess their effectiveness to minimize or prevent the de-bonding of these externally applied composite materials. This paper outlines the findings of the research program and describes the effectiveness of different application configurations including thickness of the fibre composites, pre-treatment of the beams, geometric alignment and type of fibre, and different end anchorages. A comparison of the load-deflection and failure mechanism of the fibre strengthened beams with non-fibre strengthened beams is presented. Preliminary results indicate that the fibre strengthened beams had improved strength characteristics when compared with non composite beams. However, the fibre reinforced composite concrete beams exhibited non ductile failures which suggest the need for further research to resolve these matters when designing the fibre post-strengthening system.